Gestão da informação e sistema de informações policiais em uma delegacia da polícia civil do Estado do Rio de Janeiro: uma abordagem organizacional - Diniz, Cládice Nóbile (1998)
The dissertation presents the work process of the police inquiry as heing the key process of the police information system of a police station located in the State of Rio de Janeiro. It also takes into consideration the admiministration of the information and systems analysis, by comparing the opinions of some experts, for a hetter understanding of the police organization. It also presents a general view of the organization Polícia Civil do Estado do Rio de Janeneiro nowadays as wel1 as during its past history. It descrihes the importance of the language in its organization culture and its work logics based on discoursees, and proposes some possibilities of organization changes. The so cal1ed 'research-action' was the methodology adopted, participant and ethnographic, with data processing based on information, discource contents analysis and systems theories.